Satellite pictures and low pressure areas or waves - GEORGE, C. A.; SHARMA, M. C. (MAUSAM, 1971)
A study of low pressure areas or waves, which moved across south Bay of Bengal and south Arabian Sea has been made for the year 1968. Cloud features associated with the systems as given once daily by ESSA-6 APT satellite, gave useful indications regarding intensifications, weakening and track of these low pressure systems. Utility of this correspondence for simulation of synoptic analysis over data-gap areas has been pointed out.